1996
DOI: 10.1046/j.1526-4610.1996.3603137.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Sumatriptan on Workplace Productivity, Nonwork Activities, and Health‐Related Quality of Life Among Hospital Employees With Migraine

Abstract: This prospective, open-label study evaluated the effects of subcutaneous sumatriptan versus usual therapy on workplace productivity, activity time outside of work, and health-related quality of life in 43 men or women who were hospital employees diagnosed with migraine according to international Headache Society criteria. Patients treated migraines with their usual therapy for 12 to 18 weeks followed by subcutaneous sumatriptan for 6 months. Health-related quality of life measurements obtained at baseline, aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
50
0
2

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(57 citation statements)
references
References 11 publications
5
50
0
2
Order By: Relevance
“…Similarly, patients using open-label sumatriptan injection for up to 24 months reported missing fewer work days during sumatriptan therapy (mean, 1.4 days in the past 4 weeks) compared with baseline (presumatriptan) (mean, 2.5 days in the past 4 weeks). 14 The data from this placebo-controlled study also corroborate the results of 2 open-label studies 5,6 that used lost workplace productivity measures similar to those in the present trial. Mushet and colleagues 5 found that lost workplace productivity was 38% lower over a 6-month period in which 43 patients used sumatriptan injection (6 mg) to treat migraines compared with the preceding 12-to 18-week period during which patients used their usual (nonsumatriptan) therapy.…”
Section: Commentsupporting
confidence: 77%
See 1 more Smart Citation
“…Similarly, patients using open-label sumatriptan injection for up to 24 months reported missing fewer work days during sumatriptan therapy (mean, 1.4 days in the past 4 weeks) compared with baseline (presumatriptan) (mean, 2.5 days in the past 4 weeks). 14 The data from this placebo-controlled study also corroborate the results of 2 open-label studies 5,6 that used lost workplace productivity measures similar to those in the present trial. Mushet and colleagues 5 found that lost workplace productivity was 38% lower over a 6-month period in which 43 patients used sumatriptan injection (6 mg) to treat migraines compared with the preceding 12-to 18-week period during which patients used their usual (nonsumatriptan) therapy.…”
Section: Commentsupporting
confidence: 77%
“…4 By relieving symptoms and reducing disability, an effective migraine therapy should counteract migraine-associated productivity loss. In fact, the 5-hydroxytryptamine-agonist sumatriptan succinate used for 6 months in each of 2 open-label studies 5,6 was associated with 30% to 38% reductions in lost workplace productivity compared with 2 to 4 months of patients' usual (nonsumatriptan) therapy. Although these data suggest that effective treatment of migraine with sumatriptan reduces productivity losses attributed to migraine, the open-label design of these studies does not allow unequivocal attribution of the reduction in lost workplace productivity to sumatriptan.…”
mentioning
confidence: 99%
“…After six to nine months of follow-up, the comparison of the pretreatment and the follow-up SF-36 showed significant improvement of three domains of the questionnaire: bodily pain, social function and role functioning. Mushet et al [26] reported significant improvement of the score of the role emotional dimension of the Short Form-36 after sumatriptan compared to usual therapy. The results of this study showed that the majority of the domains of SF-36 (except for physical function and role emotional) improve with the intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Novas drogas desta família, mais eficientes e com menos efeitos colaterais, poderão em breve contribuir para melhorar estes índices. Mesmo o uso do sumatriptan, um medicamento comparativamente mais caro, mostrase compensador, tendo em vista a redução dos custos indiretos 33 . Em um levantamento entre 220 indivíduos que usaram sumatriptan injetável, cerca de 2/3 eram empregados em tempo integral.…”
Section: Discussionunclassified